SUBGENRES OF THE ALTERNATIVE HISTORY NOVEL: POETICS AND GENEALOGY - Antonina V. Anistratenko (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article deals with the basic characteristics of the alternative history subgenres, its style, metagenre markers, and common plot characteristics. The meta-genre of alternative history (AH) is presented here as the basic gender formation that derives its own subgenres with similar and different markers. The aim of the article is to determine how the special gender complexes and stylistic markers that form the AH are identified as a subgenres of the alternative history meta-genre in Ukrainian and in American literature dimensions. To present AH subgenre classifications description methods are used; to analyze and divide them for the classification improvement of gender and stylistic elements of AH subgenres the comparative method and the analytical principle were involved. It could be concluded that the AH meta-genre formation itself has been separated into individual sub-genres and varieties over time and has accepted different fable schemes from the other genres, particularly the canonical ones, such as historical novel, fiction novel, detective novel, uchronic and fantasy. Alternative history has become emergency aid for the restoration of a much-needed myth in Europe. Alternative history and histories try to overcome this sacralization and make each European component an alternative one. In American literature, alternative history plays the role of rebuilding national history and making future visions.